Effects of pulsation to the mean field and vortex development in a backward-facing step flow - Dol, Sharul Sham; Mehdi Salek, M.; Martinuzzi, R. (The American Society of Mechanical Engineers, 2014)
This work is concerned with the behavior of pulsatile flows over a backward-facing step geometry. The paper mainly focuses on the effects of the pulsation frequency on the vortex development of a 2:1 backward-facing step for mean Reynolds number of 100 and for 0.035 ≤ St ≤ 2.19. The dependence of the flow field on the Reynolds number (Re = 100 and 200) was also examined for a constant Strouhal number, St of 1. A literature survey was carried out and it was found that the pulsation modifies the behavior of the flow pattern compared to the steady flow. It was shown in the present work that the inlet pulsation generally leads to differences in the mean flow compared to the steady field although the inlet bulk velocity is the same due to energy redistribution of the large-scale vortices, which result in nonlinear effects. The particle-image velocimetry results show that the formation of coherent structures, dynamical shedding, and transport procedure are very sensitive to the level of pulsation frequencies. For low and moderate inlet frequencies, 0.4 ≤ St ≤ 1, strong vortices are formed and these vortices are periodically advected downstream in an alternate pattern. For very low inlet frequency, St = 0.035, stronger vortices are generated due to an extended formation time, however, the slow formation process causes the forming vortices to decay before shedding can happen. For high inlet frequencies, St ≥ 2.19, primary vortex is weak while no secondary vortex is formed. Flow downstream of the expansion recovers quickly. For Re = 200, the pattern of vortex formation is similar to Re = 100. However, the primary and secondary vortices decay more slowly and the vortices remain stronger for Re = 200. The strength and structure of the vortical regions depends highly on St, but Re effects are not negligible.